Bryophyllum pinnatum leaves ethanol extract inhibit maturation and promote apoptosis of systemic lupus erythematosus BALB/c mice B cells (Faculty of Medicine Universitas Indonesia, 2017)
Background: B cells play a key role in systemic lupus erythematosus (SLE). Targeting B cells as SLE therapy is a plausible approach. This study investigated the potential effects of Bryophyllum pinnatum leaves with ethanol extract in decreasing percentages of maturation, increasing percentages of apoptosis, and decreasing NF-κB p65 expressions of SLE BALB/c mice B cells. Methods: Culturing B cells from pristane induced SLE BALB/c mice's spleen will resulted in this in vitro study. B cells were activated by BAFF, LPS, IL-4, and anti-CD40 yielding CD19+ >80%. B cells were cultured by adding those stimulants with and without B. pinnatum leaves (0, 0.02, 0.1, or 0.5 µg/ml) for 72 hours at 37°C. Flow cytometry was performed to determine The Percentages of maturation (CD19+CD38+) and apoptosis (Annexin V+PI+) of B cells. Further analysis to determine the expressions of transcription factor of maturation and apoptosis of B cells, NF-κB p65, were performed using immunocytochemistry. Data were analyzed using SPSS version 22. Results: Flow cytometry assay showed significant decrease in percentages of maturation of B cells in all doses and significant increase in percentage of apoptosis of B cells in dose 0.5 µg/ml. Immunocytochemistry results showed significant decrease expressions of NF-κB p65 in all doses. Percentages of maturation, apoptosis, and expressions of NF-κB p65 of B cells were significantly correlated. Conclusion: This in vitro study revealed that B. pinnatum leaves with ethanol extract decreased the percentages of maturation, increased the percentage of apoptosis, and decreased NF-κB p65 expressions of SLE BALB/c mice B cells significantly.